Electronic Networking System With Laser Light To Detect And Repel Sparrow Pests - Nuracantha, Luqyana Aufa; Kharisma, Oktaf Brilian; Simaremare, Harris; Ismaredah, Ewi (PROtek : Jurnal Ilmiah Teknik Elektro, 2025)
Rice is one of the staple foods of the Indonesian population and has an important role in the formation of the Gross Domestic Product (GDP). However, this role has not been able to run well because many pests attack and cause crop failure, one of which is sparrow pests. For this reason, a study was conducted using ultrasonic sound to disturb the pests so that they do not land and leave the rice plant. The ultrasonic sound is emitted when the bird approaches and breaks the electronic net of the laser beam spread over the rice plant. This prototype was built using the NodeMCU ESP32 microcontroller as the controller and system. And telegram is used as a supporting application to give on/off commands and battery percentage detectors to facilitate use. According to the the research, the prototype functions properly and the disturbed by ultrasonic sound with frequencies ranging from 0 - 22,000 Hz and sound pressure levels between 31.6 - 93.2 decibels.